An investigation into revenge pornography - Dias, Ana (2024)
The aim of this thesis was to contribute to the understanding and knowledge of revenge pornography behaviours. A systematic review, two empirical studies and a methodology and psychometric critique were undertaken to achieve this. An overview of the literature on revenge pornography is presented within chapter one, which clarifies its definition and the construct in which revenge pornography can be understood. In chapter two, factors associated with revenge pornography behaviours are systematically reviewed. Implications for intervention and research are highlighted in light of the findings. Chapter three critiques the methodology used within this thesis. It also examines the psychometric properties of the Experiences in Close Relationships questionnaire (Brennan et al., 1998) and the Reflective Functioning questionnaire (Fonagy et al., 2016), which were used in the empirical studies presented in chapters four and five respectively. Chapter four presents an empirical study exploring the attachment styles of revenge pornography perpetrators (n=529) and victims (n=312), while chapter five explores the mentalizing capacities using the same sample of revenge pornography perpetrators and victims. Although the studies in chapters four and five used the same sample, data was analysed separately. Chapter six presents a general discussion of this thesis, where the main findings from each individual chapter are consolidated, and theoretical frameworks are used to interpret and discuss the key findings of this thesis. Implications for future research and limitations of the thesis are also discussed.